Synthesis of Quasicrystal Al66Cu28Fe15B7 by Melt-Spinning - Luciano Nascimento (Orbital: The Electronic Journal of Chemistry, 2021)
The melt-spinning process, for printing high cooling rates, is one of the main means for obtaining quasicrystalline alloys. Therefore, in this work this method was used to study the development of the quasicrystalline alloy Al66Cu28Fe15B7. In this sense, the alloy was initially manufactured, in the respective compositions, by fusion, under an argon atmosphere, in an induction furnace, to then be subjected to the melt-spinning process, where the material was obtained in the form of tape. The sample was characterized by X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM). The result indicated the transformation formation of the i-AlCuFeB→ω-Al7Cu2Fe phases as a function of the β-Al13Cu4Fe3 cubic phase, and a probable contribution of boron to the stability of the icosahedral phase.DOI: http://dx.doi.org/10.17807/orbital.v13i3.1591